Pembinaan Penggunaan Whatsapp Business Kepada Pelaku Bisnis Online di Desa Cileungsi - Septia B., Rico; Nurhasan, Nurhasan; Baharsyah, Syamsudin (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The digital era opens opportunities for business people to promote their business on digital platforms such as social media, one of which is Whatsapp Business (business WA). Due to the lack of online promotion practices and lack of knowledge, this is of course an obstacle for business actors in running their business. In this service activity, the team shared information and introduced WA business as an application that allows business interaction between business actors and customers or prospective customers, besides that they were provided with direct practice related to business WA installation and proper management methods. This activity aims to deepen understanding regarding the use of business WA as a promotional medium and improve skills in managing business WA. Service partners are 20 business actors. The method used to determine the increase in marketing using descriptive quantitative methods, namely research methods using quantitative data and described descriptively. Most of the activity participants received increased knowledge and abilities after receiving material in the Community Service activities. In fact, some activity participants received a fairly high increase of up to 44% compared to before participating in the activity. Based on the Community Service activities that have been carried out, it is concluded that this Community Service activity deepens understanding regarding the use of business WA as a promotional medium and improves skills in managing business WA as a promotional medium in business activities.